Association between hip joint impingement and lumbar disc disease in elite rowers - Wedatilake, T.; Palmer, A.; Fernquest, S.; Redgrave, A.; Arnold, L.; Kluzek, S.; McGregor, A.; Teh, J.; Newton, J.; Glyn-Jones, S. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives Lumbar disc disease is a known cause of back pain. Increasingly it is thought that cam morphology of the hip may have a causal role in development of lumbar disc disease. The aim of this study was to describe the morphology of the hip and investigate the association of cam morphology with lumbar disc disease observed on MRI in elite rowers.